2019
DOI: 10.1038/s41387-019-0078-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and diabetic foot ulcer: a systematic review and meta-analysis

Abstract: We aimed to evaluate the association between vitamin D deficiency and diabetic foot ulcer (DFU) in patients with diabetes. Pubmed, EMBASE, BIOSIS, the Cochrane Library, and Web of Knowledge, last updated in July 2018, were searched. We assessed eligible studies for the association between vitamin D deficiency and DFU in diabetic patients. The mean difference (MD) or the odds ratio (OR) was calculated for continuous or dichotomous data respectively. Data were analyzed by using the Cochrane Collaboration’s RevMa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 28 publications
0
41
0
3
Order By: Relevance
“…Additionally, previous studies have revealed that patients with DFU had higher prevalence of VDD and lower vitamin D levels in comparison to diabetic patients without DFU (17,20,45,54,55). We reported that the prevalence of VDD in participants with DFU was about 80%.…”
Section: Discussionmentioning
confidence: 59%
“…Additionally, previous studies have revealed that patients with DFU had higher prevalence of VDD and lower vitamin D levels in comparison to diabetic patients without DFU (17,20,45,54,55). We reported that the prevalence of VDD in participants with DFU was about 80%.…”
Section: Discussionmentioning
confidence: 59%
“…A randomized, double-blind, placebo-controlled trial, by Razzaghi et al, showed that vitamin D, compared with placebo, entailed a more significant improvement in wound parameters ( 22 ). We also conducted a meta-analysis to evaluate the association between vitamin D deficiency and DFU and reported a significantly reduction of vitamin D levels in DFU group when compared with DM group ( 23 ). In this study, we study the association between vitamin D, HDL-C, LDL-C, TG, and TC in blood serum on diabetic foot ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous studies have revealed that patients with DFU had higher prevalence of VDD and lower vitamin D levels in comparison to diabetic patients without DFU [17,22,70,[80][81][82]. We reported that the prevalence of VDD in participants with DFU was about 80%.…”
Section: Discussionmentioning
confidence: 61%